The Impact of the development of Bayuangga Mall combines modern MSMEs with the Green Architecture concept - Lail, Anastasia Nadliratul; Aisyah, Aisyah; Mappaturi, Andi Baso; Firmansyah, Aldrin Yusuf (Maliki Interdisciplinary Journal, 2024)
The Probolinggo government plans to build a mall combined with modern MSMEs located at Jl. A A. Maramis No.11, Kanigaran, Kec. Kanigaran, Probolinggo City, East Java 67213, where the plan is to be close to Green Open Space (RTH) which adapts to the green building concept. This concept was taken to minimize energy consumption and then environmentally friendly technology was applied based on an energy audit in accordance with Minister of Energy and Mineral Resources Regulation No. 13 of 2012. This mall is expected can support environmental sustainability and community quality of life. This mall is expected to be able to do so to boost the economy, especially local MSMEs.